The Effectiveness Of Ginger And Honey Therapy To Reduce Nausea In Ca Mammary Patients On Chemotherapy - Apriani Yanti; Lia Natalia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Chemotherapy is one of the primary treatment modalities for patients with breast cancer (Ca mammae). Despite its effectiveness, chemotherapy frequently causes side effects such as nausea, which can negatively affect patients’ quality of life and adherence to treatment. Pharmacological management is commonly used to control chemotherapy-induced nausea; however, it may not always be effective and can produce additional adverse effects. Therefore, supportive non-pharmacological interventions are needed. Ginger and honey are natural substances known for their antiemetic properties and potential to alleviate nausea.This study employed a descriptive case study design. The subjects were patients with Ca mammae undergoing chemotherapy who experienced nausea. Nausea levels were assessed using the Index of Nausea, Vomiting, and Retching (INVR) instrument before and after the administration of ginger and honey therapy. The intervention consisted of providing ginger and honey as a complementary therapy during the chemotherapy period. Data were analyzed descriptively by comparing pre- and post-intervention nausea scores. The findings demonstrated a decrease in INVR scores after the administration of ginger and honey therapy. This reduction indicates an improvement in nausea symptoms among patients with Ca mammae following chemotherapy. Discussion/Suggestion: Ginger and honey therapy was shown to be effective in reducing chemotherapy-induced nausea. This intervention may serve as a safe, simple, and cost-effective non-pharmacological nursing strategy. It is recommended that nurses consider incorporating ginger and honey therapy as a complementary intervention to support patients undergoing chemotherapy.